2000
DOI: 10.1523/jneurosci.20-20-07816.2000
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Level Cortisol Treatment Impairs Inhibitory Control of Behavior in Monkeys

Abstract: Most studies of cortisol-induced cognitive impairments have focused on hippocampal-dependent memory. This study investigates a different aspect of cognition in a randomized placebocontrolled experiment with monkeys that were treated with cortisol according to a protocol that simulates a prolonged stress response. Young adult and older adult monkeys were assigned randomly to placebo or chronic treatment with cortisol in a 2 ϫ 2 factorial design (n ϭ 8 monkeys per condition). Inhibitory control of behavior was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 77 publications
1
88
0
2
Order By: Relevance
“…Lupien et al (1999), for example, reported a U-shaped curve between performance on a working memory task and changes in cortisol levels after hydrocortisone infusion. Also animal research showed that chronic corticosterone administration and chronic behavioral stress can lead to dendritic reorganizations in the medial PFC (Wellman, 1993;Radley et al, 2004) and that exposure to stress-levels of cortisol results in impaired prefrontal behavioral control (Lyons et al, 2000). In our sample of high cortisol responders, such stress induced impairments in prefrontal executive functioning may have affected the task-performance in at least three ways.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Lupien et al (1999), for example, reported a U-shaped curve between performance on a working memory task and changes in cortisol levels after hydrocortisone infusion. Also animal research showed that chronic corticosterone administration and chronic behavioral stress can lead to dendritic reorganizations in the medial PFC (Wellman, 1993;Radley et al, 2004) and that exposure to stress-levels of cortisol results in impaired prefrontal behavioral control (Lyons et al, 2000). In our sample of high cortisol responders, such stress induced impairments in prefrontal executive functioning may have affected the task-performance in at least three ways.…”
Section: Discussionmentioning
confidence: 73%
“…Meaney and Aitken, 1985;Radley et al, 2004;Sanchez et al, 2000). Lyons et al (2000), for example, found impairments in prefrontal inhibitory control of behavior in primates after prolonged exposure to stress-levels of cortisol. Also studies among healthy young men showed pharmacologically administered cortisol to impair prefrontal functions, such as working memory (Lupien et al, 1999;Wolf et al, 2001;Young et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of an effect on visuospatial memory and motor speed suggests some specificity to cognitive flexibility; however, we cannot exclude a cognitive effect of other stress hormones. Administration of propranolol may affect complex interactions between the beta-adrenergic system and corticosteroid system, where activation of the latter has been shown to affect a number of aspects of cognition including many aspects attributed to frontal lobe function (Elzinga & Roelofs, 2005;Maheu et al, 2004Maheu et al, , 2005de Quervain, Roozendaal, Nitsch, McGaugh, & Hock, 2000;Lyons, Lopez, Yang, & Schatzberg, 2000;Skosnik, Chatterton, Swisher, & Park, 2000;Young, Sahakian, Robbins, & Cowen, 1999), perhaps indirectly by blocking adrenergic activity. The effects of corticosteroids can also include anatomical changes in the prefrontal cortex (Cerqueira et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, female rodents exposed to chronic stress in either adolescence or adulthood show reductions in neurogenesis (Barha et al, 2011). In addition, chronic CORT exposure in both young (adolescent) and older adult monkeys decreases inhibitory control in a PFC-dependent test of behavioral flexibility (Lyons et al, 2000). However, these studies were done in female monkeys who might be more sensitive to chronic CORT in adolescence.…”
Section: Introductionmentioning
confidence: 99%